Influence of etanercept on leptin and ghrelin secretion in children with juvenile idiopathic arthritis - Maciejewska-Paszek, Izabela (J Int Med Res, 2017)
OBJECTIVE: To assess possible changes in leptin and ghrelin secretion due to etanercept in juvenile idiopathic arthritis (JIA). METHODS: 50 patients with JIA and 16 age-matched controls were enrolled into this prospective, cross-sectional study. Serum leptin, total and acyl ghrelin were measured in addition to white blood cell (WBC) and lymphocyte counts. RESULTS: 25 patients received etanercept and 25 conventional therapies (including methotrexate) for JIA. There was no difference between treatment and control groups in leptin or ghrelin levels and no evidence of a relationship between leptin and ghrelin in patients with JIA. In all children with JIA there was a correlation between leptin and body mass index (BMI). However, compared with children in the conventional treatment group, children in the etanercept group showed a positive correlation between total ghrelin and BMI and those with a low BMI showed a negative correlation between acyl ghrelin and BMI. CONCLUSION: No differences in leptin and ghrelin concentrations were found when patients with JIA and controls were compared or when patients who received etanercept were compared with those who received conventional treatment for JIA.